Empreendimentos de Economia Solidária como Espaços de Emancipação Feminina - Tania Cristina Costa Calarge (2022)
Solidarity economy enterprises are spaces for collaboration and associated work in the first instance as an alternative for work, income, and survival, but they present contradictions and potentialities that point to overcoming the degrading determinations of capital. This work aims to analyze women's emancipation in relation to work and gender, and the development and support for women in Solidarity Economy ventures. The epistemic perspective is historical materialism, and the adopted method is Critical Content Analysis. As a theoretical framework, I present the conditions of relations in the world of work, the limitations, and possibilities of the Solidarity Economy, through the historical-dialectical movement and through the experiences and attempts of self-management, and I present a review of the feminist movement and the mediations and contradictions of such movement. The empirical field is self-managed enterprises led by women, linked to rural areas. The development of the ACC method allowed the proposal of four new categories for understanding the object, namely: female condition, female mystification, productive sisterhood, and female emancipation. It is concluded that capitalist and patriarchal oppressions feed and sustain each other, being essential the subversion of gender oppression to overcome class exploitation.